2016
DOI: 10.1089/zeb.2016.1252
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chronic Arsenic Exposure in Zebrafish

Abstract: Arsenic is a prevalent environmental toxin and a Group one human carcinogenic agent. Chronic arsenic exposure has been associated with many human diseases. The aim of this study is to evaluate zebrafish as an animal model to assess arsenic toxicity in elevated long-term arsenic exposure. With prolonged exposure (6 months) to various concentrations of arsenic from 50 ppb to 300 ppb, effects of arsenic accumulation in zebrafish tissues, and phenotypes were investigated. Results showed that there are no significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 59 publications
4
17
0
Order By: Relevance
“…Particularly collembolans and enchytraeids have been shown to be highly sensitive to arsenic with no observed effect concentrations (NOECs) at or below 10 mg/kg soil [93][94][95], while the plant Avena sativa and the bacterium Arthrobacter globiformis are far less susceptible [92]. The effects were most apparent in the second generation of exposed collembolans in the present study, which is in line with a recent report on transgenerational effects of arsenic in an aquatic organism, the zebrafish [96]. Hence, the impacted soil habitat quality for the collembolan and enchytraeid species at the study site clearly points at ecotoxicologically relevant concentrations of arsenic in the soil.…”
Section: Ecotoxicological Impacts Of Wastewater Applicationsupporting
confidence: 91%
“…Particularly collembolans and enchytraeids have been shown to be highly sensitive to arsenic with no observed effect concentrations (NOECs) at or below 10 mg/kg soil [93][94][95], while the plant Avena sativa and the bacterium Arthrobacter globiformis are far less susceptible [92]. The effects were most apparent in the second generation of exposed collembolans in the present study, which is in line with a recent report on transgenerational effects of arsenic in an aquatic organism, the zebrafish [96]. Hence, the impacted soil habitat quality for the collembolan and enchytraeid species at the study site clearly points at ecotoxicologically relevant concentrations of arsenic in the soil.…”
Section: Ecotoxicological Impacts Of Wastewater Applicationsupporting
confidence: 91%
“…While information about the rate of arsenic metabolism by zebrafish in vivo and the production of specific metabolites are still emerging, it is clear that rodent models do not always accurately reflect the effects of human arsenic exposure. For instance, studies in rodents showed increased excretion and slower but more extensive methylation of arsenic when compared to humans so that ingested arsenic remains in the rodent blood stream for prolonged periods (Hallauer et al, 2016; States et al, 2011). …”
Section: Pathways and Mechanisms Of Toxicant-induced Diseasementioning
confidence: 99%
“…Chronic exposure of zebrafish to environmentally relevant concentrations revealed retention of arsenic in the eye, skin, and liver of 6-month-old fish and resulted in increased heart rate during larval stages and neurologic defects (Hallauer et al, 2016). Progeny of arsenic-exposed fish had reduced biomass at 3 months of age relative to the progeny of their unexposed siblings (Hallauer et al, 2016).…”
Section: Pathways and Mechanisms Of Toxicant-induced Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…7 Hallauer et al report how chronic arsenic exposure leads to neurological dysfunction and reduced body weight in progeny from exposed adults. 8 Finally, Baker et al examine the molecular and cellular changes in the testes after exposure to the persistent organic pollutant 2,3,7,8-tetrachlorodibenzodioxin, an endocrine disruptor that exerts transgenerational effects through the male germline.…”
mentioning
confidence: 99%